Temporal dynamics of muscle mitochondrial uncoupling-induced integrated stress response and ferroptosis defense - Igual Gil, Carla; Löser, Alina; Lossow, Kristina; Schwarz, Maria; Weber, Daniela; Grune, Tilman; Kipp, Anna P.; Klaus, Susanne; Ost, Mario (Frontiers in Endocrinology, 2023)
Mitochondria play multifaceted roles in cellular function, and impairments across domains of mitochondrial biology are known to promote cellular integrated stress response (ISR) pathways as well as systemic metabolic adaptations. However, the temporal dynamics of specific mitochondrial ISR related to physiological variations in tissue-specific energy demands remains unknown. Here, we conducted a comprehensive 24-hour muscle and plasma profiling of male and female mice with ectopic mitochondrial respiratory uncoupling in skeletal muscle (mUcp1-transgenic, TG). TG mice are characterized by increased muscle ISR, elevated oxidative stress defense, and increased secretion of FGF21 and GDF15 as ISR-induced myokines. We observed a temporal signature of both cellautonomous and systemic ISR in the context of endocrine myokine signaling and cellular redox balance, but not of ferroptotic signature which was also increased in TG muscle. We show a progressive increase of muscle ISR on transcriptional level during the active phase (night time), with a subsequent peak in circulating FGF21 and GDF15 in the early resting phase. Moreover, we found highest levels of muscle oxidative defense (GPX and NQO activity) between the late active to early resting phase, which could aim to counteract excessive iron-dependent lipid peroxidation and ferroptosis in muscle of TG mice. These findings highlight the temporal dynamics of cell-autonomous and endocrine ISR signaling under skeletal muscle mitochondrial uncoupling, emphasizing the importance of considering such dissociation in translational strategies and sample collection for diagnostic biomarker analysis.